Procalcitonin, C-Reactive Protein, and Neutrophil Ratio Contribute to the Diagnosis and Prognosis of Severe Acute Pancreatitis - Yi LIANG; Xianwei ZHAO; Fanliang MENG (Tehran University of Medical Sciences, 2019)
Background: We aimed to explore the significance of procalcitonin (PCT), C-reactive protein (CRP) and neutrophil ratio (N%) in the early diagnosis, treatment, and prognosis of severe acute pancreatitis (SAP). Methods: A total of 104 patients with SAP (SAP group) and 101 patients with mild acute pancreatitis (MAP) (MAP group) admitted to Affiliated Hospital of Jining Medical University, Jining, China were enrolled. The PCT and CRP in serum were detected by a full-automatic biochemical analyzer, and N% in peripheral blood was measured by a hemocyte analyzer. Results: The peripheral blood PCT, CRP, and N% in the SAP group were significantly higher than those in the MAP group (P<0.001). Multivariate Logistic regression analysis showed that acute physiology and chronic health evaluation II (APACHE II) score, Ranson score, PCT, CRP, and N% were independent risk factors for SAP. The receiver operating characteristic (ROC) curve showed that the area under curve (AUC) of PCT, CRP, and N% in diagnosing SAP were 0.906, 0.840, and 0.834 respectively, while that of combined detection was 0.972. The AUC of PCT, CRP, and N% in diagnosing SAP death were 0.907, 0.900, and 0.894, respectively. Conclusions: Peripheral blood PCT, CRP, and N% contribute to the diagnosis and prognosis of SAP.